Content Analysis of Anies-Muhaimin Campaign in Aceh for The 2024 Presidential Election - Cut ladya Izzah; Ardiansyah Ardiansyah (Jurnal Realitas Sosial, 2025)
This study analyzes the victory of Anies Baswedan and Muhaimin Iskandar in the 2024 presidential election in Aceh Province, focusing on how their campaign strategies and content through social media influenced public perception and voting behavior. The research aims to explain how political communication conducted through both digital and mainstream media became a determining factor in shaping the political preferences of the Acehnese community. Using a descriptive qualitative approach, this study collected data through in-depth interviews, observation, and documentation. The theoretical framework is based on political communication theory and agenda-setting theory, which help explain how the media can influence the formation of public opinion and political attitudes. The findings reveal that social media platforms such as TikTok, Instagram, and Facebook became the main channels for communicating messages, building emotional connections, and strengthening the candidates’ popularity among the Acehnese people. Campaign content that emphasized religious values, moral integrity, and local identity was particularly effective in attracting attention and generating engagement. The use of regional symbols and culturally resonant narratives further enhanced the message’s authenticity and relevance. Meanwhile, mainstream media such as television, radio, and newspapers played a secondary yet important role in reinforcing credibility and delivering structured messages. However, its reach remained limited unless its content was amplified through social media sharing. In conclusion, the success of Anies Baswedan and Muhaimin Iskandar in Aceh was closely linked to their adaptive political communication strategy, which combined cultural sensitivity, emotional appeal, and strategic use of digital media to influence voter perceptions and strengthen political legitimacy.